(untitled) (UCC Student Medical Journal, 2026)
Background: The World Federation of Societies of Anaesthesiologists has established guidelines for anaesthesia in laparoscopic surgery, but detailed protocols for perioperative pain management in Robot-Assisted Laparoscopic Prostatectomy (RALP) are lacking (1). This study evaluated the analgesic efficacy of a single intrathecal morphine (ITM) dose in RALP. Methods: Following Ethics Committee approval, a retrospective chart review of 79 patient charts that underwent RALP procedures between 01/01/2021 and 31/05/2023 was conducted. One patient was excluded due to regular codeine use. Patients were divided into ITM (n=18) and non-ITM (NITM, n=60). Outcomes included recovery room pain scores, opioid requirements, time to first opioid request, 24-hour postoperative opioid consumption, opioid-related side effects, and anti-emetic usage. Data was analyzed using SPSS, with P<0.05 considered significant. Results: The median [IQR] ITM dose was 200 [50] micrograms. Pain scores in the RR and 24-hour opioid consumption were similar between groups. However, the ITM group had a longer time to first opioid request compared to the NITM group (16.64 [22.9] vs. 1.32 [7.78] hours, P=0.05). Morphine-related side effects were more frequent in the ITM group (16.7% vs. 0%, P<0.001), as was anti-emetic usage (55.6% vs. 15.3%, P=0.001). Conclusion: In conclusion, a single dose of intrathecal morphine delayed the time to first opioid request in RALP patients but was associated with higher rates of side effects and anti-emetic use. These findings highlight the need to weigh the benefits of analgesia against the potential for increased adverse effects in patients undergoing RALP. References: Iqbal H, Gray M, Gowrie-Mohan S. Anaesthesia for Robot-Assisted urological surgery. Tutorial of the week, 6 Aug 2019. https://resources.wfsahq.org/wp-content/uploads/408_english.pdf (Accessed 13 Jan 2025).